Kit Magic Maths: Assist in Enhancing the Mastering of Basic Multiplication - Muhamad Shahlyme wahid; Suziyani Binti Mohamed (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2018)
Mathematical achievement of special recovery students (MPK) is still low compared to typical students. One of the factors is due to the basic mastery of the weak operation. The purpose of this study is to study the use of the Kit Magic Maths (KMM) in helping (MPK) to master the base of the multiplication. Researchers using quantitative approaches with Stephen Kemmis and Mc Taggart models carried out two rows. A total of two participants were selected through a sampling technique aimed at a school in the district of Kuala Pilah. Participants performed basic mathematical tests multiplied by 30 items at pre-test and post-test. The content of mathematical tests using the Testing Tables (JPU) is validated by three experienced teachers over 30 years in mathematics. Data findings were analysed using descriptive analysis by percentage. The findings show that KMM can help MPK master the basic skills of multiplication. Both participants pointed out the increase in pre-test score scores by 70% for participant A and 50% for participant B after the post-test. Therefore, it is hoped that KMM will be able to extend its use to teachers at the district, state and ministry levels as an effective learning aid to the learning and teaching of MPK. Consequently, the use of KMM is seen to help MPK increase the level of basic operation of multiplicity better than before, in addition to enhancing student’s interest in mathematical subjects.